A numerical investigation into floor buckling mechanisms in underground coal mine roadways. (September 2020) - Mo, Sungsoon; Sheffield, Patrycja; Corbett, Peter; Ramandi, Hamed Lamei; Oh, Joung; Canbulat, Ismet; Saydam, Serkan
Highlights: Coal mine roadway with a strong floor unit overlying weak floor units is simulated. Results show the failure of the underlying weak unit induced the upward movements. The confinement generated by the strong floor unit reduces the floor heave. The displacements and failure modes are sensitive to the deformation modulus. Abstract: Excessive floor deformation in underground coal mines, known as floor heave, can cause production delays and thus financial losses. This paper presents parametric studies using numerical models to understand the mechanisms of floor heave in coal mine roadways. An Australian longwall coal mine that experienced significant floor heave in the roadways, where a strong floor unit overlying weak floor units is present immediately below the coal seam, was chosen for field observations. Although the relevant mechanism appears to be buckling, it is uncertain whether the displacement and the failure of the strong unit were caused by horizontal stresses exerted on the uppermost strong unit. The modelling results indicated that the failure of the underlying weak unit induced the upward movement, and subsequent deformation and failure of the overlying strong unit. The floor displacement decreased as the thickness of the overlying strong unit increased. This was attributed to the confinement generated by the strong unit. In addition, the displacement of rock and failure modes simulated by numerical models were found to be sensitive to the deformation modulus. While this numerical study suggests some degree of uncertainty about the estimation of the floor deformation still exists, the failure modes and occurrence of floor heave from numerical models were generally in agreement with the field observations. This study gives insight into floor buckling mechanisms, with the possible involvement of the underlying floor strata below the strong floor unit.